Fumigation with exogenous monoterpenes of a non-isoprenoid-emitting oak (Quercus suber): monoterpene acquisition, translocation, and effect on the photosynthetic properties at high temperatures - Delfine, Sebastiano; Csiky, Olav; Seufert, Guenther; Loreto, Francesco (New Phytologist, 2000)
We tested if fumigation with exogenous monoterpenes might induce thermotolerance in leaves of an oak species (Quercus suber) which does not form and emit isoprenoids. To understand if exogenous monoterpene fumigation results in internal accumulation of monoterpenes, a physical method of monoterpene extraction was used. The internal content of monoterpenes increased in concert with increasing fumigation doses. This unambiguously demonstrated acquisition of exogenous monoterpenes. We exposed fumigated Q. suber leaves to two cycles of increasing temperatures from 35 to 55°C at 5°C steps. When leaves were exposed to a low dose of exogenous monoterpenes, yielding an internal content similar to that endogenously formed in the leaves of the monoterpene- emitter Q. ilex, no clear improvement in thermotolerance was found. When leaves were exposed to a high dose of exogenous monoterpenes, yielding an internal content of about ®ve fold the endogenous pool of Q. ilex, but comparable with the expected content following stress-induced stomatal closure, photosynthesis inhibition at high temperatures was attenuated. This eﬀect was observed only at temperatures !45°C during the ®rst cycle, but at all temperatures between 35 and 55°C when plants were exposed to two cycles of high temperatures. Monoterpenes were still found in the leaves of Q. suber 12 h after ending the fumigation. Monoterpenes were also found in non-fumigated leaves distant up to 45 cm from the fumigated leaves. If monoterpenes make the photosynthetic apparatus more resistant to high temperatures, the eﬀect might not be limited to the fumigated leaves and might be persistent after fumigation.
Keywords: isoprenoid emission; Monoterpenes; photosynthesis; Quercus suber; thermotolerance

Fumigation with exogenous monoterpenes of a non-isoprenoid-emitting oak (Quercus suber): monoterpene acquisition, translocation, and effect on the photosynthetic properties at high temperatures (New Phytologist, 2000)
We tested if fumigation with exogenous monoterpenes might induce thermotolerance in leaves of an oak species (Quercus suber) which does not form and emit isoprenoids. To understand if exogenous monoterpene fumigation results in internal accumulation of monoterpenes, a physical method of monoterpene extraction was used. The internal content of monoterpenes increased in concert with increasing fumigation doses. This unambiguously demonstrated acquisition of exogenous monoterpenes. We exposed fumigated Q. suber leaves to two cycles of increasing temperatures from 35 to 55°C at 5°C steps. When leaves were exposed to a low dose of exogenous monoterpenes, yielding an internal content similar to that endogenously formed in the leaves of the monoterpene- emitter Q. ilex, no clear improvement in thermotolerance was found. When leaves were exposed to a high dose of exogenous monoterpenes, yielding an internal content of about ®ve fold the endogenous pool of Q. ilex, but comparable with the expected content following stress-induced stomatal closure, photosynthesis inhibition at high temperatures was attenuated. This eﬀect was observed only at temperatures !45°C during the ®rst cycle, but at all temperatures between 35 and 55°C when plants were exposed to two cycles of high temperatures. Monoterpenes were still found in the leaves of Q. suber 12 h after ending the fumigation. Monoterpenes were also found in non-fumigated leaves distant up to 45 cm from the fumigated leaves. If monoterpenes make the photosynthetic apparatus more resistant to high temperatures, the eﬀect might not be limited to the fumigated leaves and might be persistent after fumigation.